The barefoot book of children - Strickland, Tessa; Dean, David, 1976-; DePalma, Kate. (Cambridge, MA : Barefoot Books, 2016)
Text and illustrations look at different children from around the world.
Kirkus Review
Pub Weekly
Kirkus Review, August 2016
Pub Weekly, September 2016
3.0
Preschool.
Keywords: Children -- Cross-cultural studies -- Juvenile literature; Children -- Juvenile literature; Children; Children